Safety management on crime prevention at parking area in shopping mall / Fadhlin Junaidi - Junaidi, Fadhlin (Faculty of Architecture, Planning and Surveying, 2013)
We live with crime every day. Unfortunately, it has become a fact of life. Discussions on the subject have traditionally focused much more on the arrest and punishment than on crime prevention measures that cannot be taken until after a crime has been committed. Preventing crime offers tremendous savings to everyone. Enter a new approach to crime prevention is Crime Prevention through Environmental Design or CPTED is one the main aspects to prevent the crime. For this study the CPTED is relating and including to the parking facilities that an help in preventing the crime. As all know,parking is one of the popular area which contribute to the crime such as snatch, raped, theft and others.Thus, it shows that how dangerous was the parking especially when people are walking alone. The used of good facilities such as access control, signage, CCTV, panic button and other devices can control the unauthorized persons during at the parking cars. It covers he surveillance, target hardening, access control,activity support and the management in the parking. Its means Crime Prevention through Environmental Design (CPTED) can be used as a part of the parking functions. CPTED principles are applied easily and inexpensively during building or remodeling projects and have been implemented in communities across the nation.